(untitled) (Research, Society and Development, 2019)
With the objective to evaluate the effect of defoliation frequency (14, 21, 28, 35, 42 and 49 days) on green dry matter (GDM) yield, chemical composition and morphogenetic and structural characteristics of Megathyrsus maximus cv. Zuri pastures were carried out an experiment under natural field conditions at Roraima´s savannas. The reduction in the frequency of defoliation resulted in higher yields of GDM and regrowth vigor, however, it resulted in significant decreases in nitrogen, phosphorus, calcium, magnesium and potassium contents. The leaf appearance and leaf expansion rates are inversely proportional to the defoliation frequency, occurring the inverse for number of leaves tiller-1, average leaf length, leaf area index and foliar senescence rate. Maximum GDM yields, regrowth yields, number of leaves tiller-1, average leaf length and leaf area index, they were obtained with defoliation frequencies at 40.3; 44.9; 36.9; 42.4 and 39.0 days, respectively. These data suggest the frequency of defoliation more adequate for pastures of M. maximus cv. Zuri, aiming to reconcile production, regrowth vigor, quality and efficiency of forage utilization, tissue renewal and canopy structure more favorable to grazing, is between 35 and 42 days.